2012
DOI: 10.33899/edusj.2012.58993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Periodontal Status among Premenopausal and Postmenopausal Women in Mosul City

Abstract: To increase the understanding of oral health factors associated with menopause women, this research sought to examine the oral hygiene including clinical parameters (DMFT, gingival, calculus, plaque and pocket depth indices) and physical parameters (flow rate and pH) to show changes in postmenopausal women in Mosul City center in relation to premenopausal women.The sample chosen included 123 women 47 premenopausal and 76 postmenopausal women in age range from 30 -61 years old. Clinical examination was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…The present study found no differences in oral hygiene between perimenopausal and postmenopausal women (Table 3); however, the mean oral hygiene level in both groups of women was moderate (Table 2), and oral hygiene is associated with oral health, which is becoming a public health concern [38]. In the present study, the plaque and papilla bleeding indices were higher in Pesqui.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…The present study found no differences in oral hygiene between perimenopausal and postmenopausal women (Table 3); however, the mean oral hygiene level in both groups of women was moderate (Table 2), and oral hygiene is associated with oral health, which is becoming a public health concern [38]. In the present study, the plaque and papilla bleeding indices were higher in Pesqui.…”
Section: Resultscontrasting
confidence: 45%
“…found significant differences in the calculus index, plaque index, pocket depth, and salivary flow between premenopausal and postmenopausal women [38].…”
Section: Resultsmentioning
confidence: 85%
“…12 A number of studies have related menopause with some periodontal conditions. 1,[6][7][8][9]11,12,18,19 In the present study, pre and postmenopausal women were compared. First, the present findings indicate that women after menopause experienced more physical and emotional changes.…”
Section: Discussionmentioning
confidence: 99%
“…1,6-10-12 Few research in women have reported risk of developing destructive periodontal disease and poor quality of life after menopause. 1,7,11,12 On the contrary, in three studies authors stated that menopause did not appear to significantly influence the severity of periodontal disease and tooth loss. [8][9][10] So far, there is no consensus for an increased risk of periodontitis after menopause.…”
Section: Introductionmentioning
confidence: 88%
“…Estrogen and androgen hormones are present in the periodontium, so postmenopausal hormone imbalances will affect the periodontium. The decrease in the hormone estrogen causes changes in immune function and the ecology of microorganisms in the body, especially in the oral cavity [33][34][35]. Microcirculation in the postmenopausal oral cavity shows that the diameter of the loops, tortuosity of blood vessels in the labial mucosa, and changes in the density of the periodontal mucosa predispose to periodontal inflammation [36].…”
Section: Periodontal Changementioning
confidence: 99%